Case Report: Neurodevelopmental Outcome in a Small-for-Gestational-Age Infant With Symptomatic Hyperinsulinemic Hypoglycemia, Gaze Preference, and Infantile Spasms - Chandran, Suresh; Teoh, Kok Wooi; Janardhan, Krishnappa; Yap, Fabian (Frontiers in Endocrinology, 2022)
Recurrent and profound hypoglycemia is a leading cause of neonatal brain injury. Small-for-gestational-age infants are at risk of hypoglycemia due to substrate deficiency and hyperinsulinism. Inappropriate insulin secretion by the β-cells of the pancreas results in hypoglycemia, neuronal energy deprivation, and parieto-occipital brain injury. Hypoglycemic neuronal injury is increasingly being identified as a trigger for infantile spasms, even though the underlying pathophysiological mechanisms remain elusive. A term, small-for-gestational-age male infant developed severe symptomatic hypoglycemia on day 3 of life. He required a high glucose infusion rate (14 mg/kg/min) to maintain normoglycemia. Critical blood samples showed inappropriate insulin levels while hypoglycemic and hypoketonemic, consistent with a diagnosis of hyperinsulinemic hypoglycemia. Blood glucose levels normalized with a diazoxide dose of 5 mg/kg/day. Gradually, glucose infusion was weaned with increasing oral feeds while maintaining prefeed capillary blood glucose levels. While at home, his glucose profile remained stable on the self-weaning dose of diazoxide. He passed a resolution fasting study at 4 months of age after weaning off diazoxide. He developed left gaze preference at 2.5 months of age while on treatment for hyperinsulinemic hypoglycemia but developed infantile spasms at 5 months that was confirmed with an electroencephalogram (EEG). Gaze preference may be epileptic, even in the absence of seizures. Spasms were well controlled with high-dose prednisolone therapy. At the age of 6 years, he has a mild fine motor delay and learning disabilities. Early diagnosis and treatment of infantile spasms have a better prognosis. Identifying gaze preference as a predating sign of occipital lobe epilepsy, EEG monitoring, and, if required, treatment could have possibly averted the genesis of infantile spasms.